ANALISIS IMPLIKASI WEWENANG MAHKAMAH KONSTITUSI DALAM MELAKUKAN PENGUJIAN KONSTITUTIONAL TERHADAP RATIFIKASI PERJANJIAN INTERNASIONAL PADA KELEMBAGAAN DAN PUTUSAN - Ihsanudin, Muhammad; Firdaus, Sunny Ummul (Res Publica: Jurnal Hukum Kebijakan Publik, 2019)
This study analyzes and examines the implications of the authority of the Constitutional Court in conducting constitutional review of international agreements on institutions and verdict. This research is a doctrinal research that is of a nature perspective, with a statute approach, a comparative approach and a conceptual approach. The type of data collected consists of primary legal material and secondary legal material. The data collection technique used is library research. The technical analysis used is a syllogism method that uses a deductive mindset. The results showed that the implications of constitutional review of international treaties by the Constitutional Court were adjustments to the authority of the Constitutional Court, with several alternative constitutional compalint constructions, constitutional previews and statements explicitly in the constitution, the construction of which could be formed in the Constitution of the Republic of Indonesia. review of international agreements if deemed unconstitutional are acts of denunciation through internal procedures.